С.Буяннэмэх судлалын анхны хуудас: First page of Buyannemekh study - Ван Мандуга (Mongolian Studies, 2023)
The author judged few questions about works and biography of S.Buyannemekh from the works published in 1929 and 1935. According to these investigations, S.Buyannemekh was a great figure of the beginning period of modem Mongolian literature.